2023
DOI: 10.1101/2023.07.13.548917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Origin and diversity ofCapsella bursa-pastorisfrom the genomic point view

Abstract: Background: Capsella bursa-pastoris, a cosmopolitan weed of hybrid origin, is an emerging model object for the study of early consequences of polyploidy, being a fast growing annual and a close relative of Arabidopsis thaliana. The development of this model is hampered by the absence of a reference genome sequence. Results: we present here a subgenome-resolved chromosome-scale assembly and a genetic map of the genome of Capsella bursa-pastoris. It shows that the subgenomes are mostly colinear, with no massive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Like in M. sookensis , the availability of genome-wide sequence data and/or reference genomes has recently overturned or clarified the origin stories of several other wild and domesticated polyploid species. A high-quality reference genome for Capsella bursa-pastoris , for instance, helped uncover evidence of a homeologous exchange event that appears to have evolved very early in the species’ evolutionary history (the exchange is geographically widespread and present in all studied accessions), suggesting that one origin with subsequent introgression from diploid progenitors might be more likely than multiple origins (Penin et al, 2023). In Arabidopsis suecica , the story is reversed with multiple origins now inferred from extensive shared variation with its diploid progenitors (Novikova et al, 2018), instead of the single origin suggested by earlier studies of microsatellite variation (Jakobsson et al, 2006) In crops too, recent genomic analysis has begun to clarify what are often very complex evolutionary origins involving multiple rounds of hybridization between several different progenitors (e.g., bread wheat: Liu et al, 2022; Pont et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like in M. sookensis , the availability of genome-wide sequence data and/or reference genomes has recently overturned or clarified the origin stories of several other wild and domesticated polyploid species. A high-quality reference genome for Capsella bursa-pastoris , for instance, helped uncover evidence of a homeologous exchange event that appears to have evolved very early in the species’ evolutionary history (the exchange is geographically widespread and present in all studied accessions), suggesting that one origin with subsequent introgression from diploid progenitors might be more likely than multiple origins (Penin et al, 2023). In Arabidopsis suecica , the story is reversed with multiple origins now inferred from extensive shared variation with its diploid progenitors (Novikova et al, 2018), instead of the single origin suggested by earlier studies of microsatellite variation (Jakobsson et al, 2006) In crops too, recent genomic analysis has begun to clarify what are often very complex evolutionary origins involving multiple rounds of hybridization between several different progenitors (e.g., bread wheat: Liu et al, 2022; Pont et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the only wild polyploid systems with abundant population genomic data (species in Arabidopsis and Capsella ), the question of evolutionary origins has been challenging to resolve. For example, in C. bursa-pastoris , support has been equivocal for multiple origins vs. a single origin with admixture from diploid relatives (Douglas et al, 2015; Kryvokhyzha et al, 2019), though a recent discovery of an early homeologous exchange event shared species-wide might provide evidence for the latter (Penin et al, 2023). In the allotetraploid A. suecica , early evidence from microsatellite markers had suggested a unique origin (Jakobsson et al, 2006), but more recent, whole-genome population resequencing revealed extensive shared polymorphism with diploid progenitors, suggesting multiple founding individuals (Novikova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%